2020
DOI: 10.1186/s40478-020-01007-3
|View full text |Cite
|
Sign up to set email alerts
|

Distinct tissue injury patterns in juvenile dermatomyositis auto-antibody subgroups

Abstract: Introduction: Juvenile dermatomyositis (JDM) can be classified into clinical serological subgroups by distinct myositis-specific antibodies (MSAs). It is incompletely understood whether different MSAs are associated with distinct pathological characteristics, clinical disease activities, or response to treatment. Methods: We retrospectively reviewed clinicopathological data from consecutive JDM patients followed in the pediatric rheumatology clinic at a single center between October 2016 and November 2018. Dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Anti-NXP-2 was distinctively associated with microinfarctions, features described in regional ischemic immune myopathy (RIIM). 26 Although few cases have been reported describing muscle ischemia or clustered necrosis in juvenile anti-NXP-2 DM, 18, 19 we provide the first evidence that adult and juvenile anti-NXP-2 DM were equally affected by microinfarction. Since the percentage of microinfarctions in adult and juvenile anti-NXP-2 DM were not significantly different, this phenomenon could not simply be explained by different CFRs between the two age groups.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Anti-NXP-2 was distinctively associated with microinfarctions, features described in regional ischemic immune myopathy (RIIM). 26 Although few cases have been reported describing muscle ischemia or clustered necrosis in juvenile anti-NXP-2 DM, 18, 19 we provide the first evidence that adult and juvenile anti-NXP-2 DM were equally affected by microinfarction. Since the percentage of microinfarctions in adult and juvenile anti-NXP-2 DM were not significantly different, this phenomenon could not simply be explained by different CFRs between the two age groups.…”
Section: Discussionmentioning
confidence: 55%
“…16,17 Conversely, DMSA-associated pathological phenotypes have been limited to small studies. 8, 11-13,18,19 This study aimed to investigated and characterize DMSA-specific pathological features.…”
Section: Introductionmentioning
confidence: 99%
“…Mi‐2 + patients had more primary inflammation, NXP2 + patients had less primary inflammation and TIF1γ + patients had more mitochondrial dysfunction 13 . Nguyen et al also reported the MSA specific tissue injury and speculated that there might be tissue specific receptors for the different types of MSA 22 …”
Section: Discussionmentioning
confidence: 99%
“…21 Allenbach et al observed that only anti-MDA5 DM showed numerous nitric oxide synthase 2-positive muscle fibers with sarcoplasmic, not classic DM, also indicating the different pattern of mitochondrial 13 Nguyen et al also reported the MSA specific tissue injury and speculated that there might be tissue specific receptors for the different types of MSA. 22 IFN appears to play a key role in the pathogenesis of idiopathic inflammatory myopathies, especially in DM. 23 An up-regulated IFN signature has been observed in skeletal muscle, skin samples, and peripheral blood mononuclear cells of anti-MDA5 DM.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] Previous data have shown that anti-NXP2 autoantibodies are present in 23% to 30.2% of juvenile DM and less than 17% of adult PM/DM. [ 9 , 11 ] In an Argentine pediatric myositis cohort, anti-NXP2 antibodies were likely linked to muscle contractures, atrophy and significant functional compromise. [ 12 ] Additionally, anti-NXP2 autoantibodies detected in DM were found to be more significantly associated with calcinosis in younger patients and cancer in older male adults.…”
Section: Discussionmentioning
confidence: 99%